Voices of special need students at public higher learning institutions: a wishlist to ponder / Zurina Ismail ... [et al.] - Zurina Ismail, Zurina Ismail; Muhamad Zaki, Nur Haziqah; Ahmad, Abdul Aziz; Zakaria, Azzarina (UiTM Press, 2024)
The global movement towards inclusive and equitable education has gained significant momentum in recent years. This study delves into the aspirations and challenges of special needs students in Malaysian public universities, aiming to provide insights into their expectations and experiences. Through qualitative research methods, via semi-structured online interviews and thematic analysis, this study uncovers several key themes. First, the study highlights concern regarding inadequate infrastructure and facilities within higher education institutions. Participants emphasized the need for infrastructure that caters to diverse disabilities, revealing a gap between policy and implementation. Secondly, equitable treatment emerged as a paramount concern. Special needs students desire fair and respectful treatment from peers, lecturers, and employers. Thirdly, the need for greater awareness and understanding of special needs students’ unique needs and capabilities is emphasized. Fourthly, participants highlighted the importance of robust support systems, including academic assistance and counselling services. Fifthly, fostering empathy among peers, family, and special needs students themselves is critical. E-learning is proposed as an intervention to support inclusivity of the special needs students at higher learning institution. E-learning provides equitable access to educational resources- it contributes to equal treatment by offering standardized interfaces and incorporating universal design principles, raises awareness through disability awareness modules and asynchronous communication, fosters greater understanding among peers and educators, integrates virtual support services, ensures tailored guidance for special needs students, and creates opportunities for collaborative learning experiences. Clear and enforced policies are crucial to safeguard the rights of special needs students and can facilitate policy dissemination and enforcement by serving as a centralized platform for communication.